1990
DOI: 10.1136/bmj.300.6726.705
|View full text |Cite
|
Sign up to set email alerts
|

Medical problems of adults who were sexually abused in childhood.

Abstract: The aim of the study was to see whether adults who had been sexually abused in childhood were vulnerable to physical symptoms and therefore investigation and intervention.The case histories of seven patients who were aged 22-39, were under the care of three consultant psychiatrists, had experienced childhood sexual abuse, and had a history of medical or surgical intervention were surveyed. The patients had had a mean of 18 contacts with non-psychiatric consultant teams and a mean of eight operations, with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 15 publications
2
53
1
Order By: Relevance
“…This finding is consistent with the findings of other reports, although some found that not only physical abuse survivors but also sexual abuse survivors are more likely than nonabused patients to report somatic symptoms (Arnold et al, 1990;Ross et d., 1990;Drosman et d., 1990;Williams et al, 1992;Pribr et al, 1993;Anderson et d., 1993). The reason that patients with sexual abuse histories in our study did not complain about somatic symptoms more than those Y. Ono et al…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the findings of other reports, although some found that not only physical abuse survivors but also sexual abuse survivors are more likely than nonabused patients to report somatic symptoms (Arnold et al, 1990;Ross et d., 1990;Drosman et d., 1990;Williams et al, 1992;Pribr et al, 1993;Anderson et d., 1993). The reason that patients with sexual abuse histories in our study did not complain about somatic symptoms more than those Y. Ono et al…”
Section: Discussionsupporting
confidence: 92%
“…Several groups, using various methods, have reported an increase in a range of psychiatric disorders [1]. Some attention has also been paid to unexplained medical symptoms, those clinically challenging conditions whose pathology is not clearly understood and whose treatment is often difficult [2, 3, 4, 5, 6]. The focus has been particularly on chronic pelvic pain [7, 8, 9, 10, 11]and so-called functional gastro-intestinal disorders, especially irritable bowel syndrome [12, 13, 14, 15, 16, 17, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus sexual abuse survivors' distress is compounded: they may find themselves dismissed as hypochondriacs, as 'Munchausens', as troublemakers, or as 'heartsink' patients. Alternatively, as Arnold et al (1990) graphically showed (even measuring the thickness of their medical files! ), they may undergo years of repeated, needless or damaging examinations and surgery.…”
Section: 'The Direct Effects Of Violence and Injury Repeated Over Yementioning
confidence: 99%